Action and adventure cinema - Tasker, Yvonne, 1964- (Routledge, 2004)
Addressing areas such as genre, film history and style, action and spectacle, stars and bodies, action auteurs and the film industry, the reader covers both Hollywood and also European and Asian action cinema.